The SMARCA4–TMEM47 axis plays an essential role in chikungunya virus RNA replication - Yu-Zhi Fu; Fang-Fang Luo; Liu Yang; Jing-Yang Li; Bo-Wen Zhang; Zhen-Qi Li; Li-Xin Zhao; Su-Yun Wang; Yan-Yi Wang (Proceedings of the National Academy of Sciences, 2026)
Chikungunya virus (CHIKV) poses an ongoing threat to global public health. Here, we identified the cBAF complex core ATPase subunit SMARCA4 as a host factor for CHIKV. SMARCA4 acts as a chromatin remodeling factor to license expression of the four-pass transmembrane protein TMEM47. TMEM47 deficiency impairs CHIKV replication in divergent cell types and reduces viral loads and pathological effects following CHIKV infection in mice. TMEM47 interacts with both CHIKV RNA and the nonstructural protein nsP1. Ectopic expression of nsP1 causes a marked redistribution of TMEM47 to the plasma membrane, where it is required for successful assembly of viral replication spherules. We also show that the SMARCA4 inhibitors inhibit CHIKV replication in cells. These findings suggest that the SMARCA4–TMEM47 axis plays an essential role for the completion of the CHIKV life cycle and can be a potential target for anti-CHIKV therapeutics.